Identification of Antibacterial Compounds in Black Garlic against Salmonella typhimurium using HPLC-Fingerprinting and Chemometrics - Abiyyuddin, M. Farras; Rahayu, Winiati P; Yuliana, Nancy Dewi; Setiawan, Abdul Aziz; Anggraeni, Ririn; Marwanta, Edy; Marasabessy, Ahmad (Universitas Jenderal Soedirman, 2025)
ABSTRACT. Black garlic is an aged product derived from fresh garlic and exhibits potential antibacterial properties. This study aims to identify the antibacterial compounds in black garlic against Salmonella typhimurium using HPLC fingerprinting and chemometrics. The antibacterial activity of the n-hexane fraction, methanol fraction, and water fraction were analyzed using the well diffusion method. Only the water fraction exhibited an inhibitory zone against S. typhimurium of 11.96 ± 1.86 mm. The chemical profile of each fraction, analyzed by HPLC-MWD, was correlated with antibacterial activity data using Orthogonal Projection to Latent Structure. A retention interval of 2.50 – 2.99 and 2.00 – 2.49 minutes of the water fraction at a wavelength of 214 nm demonstrated a correlation with antibacterial activity. The peaks identified in HPLC-MWD at a retention interval of 2.50 – 2.99 and 2.00 – 2.49 minutes exhibited a similar pattern to the peaks appearing at a retention time of 1.12 and 1.06 minutes on the UHPLC-Q-Orbitrap-HRMS chromatogram. The resultant peak in the UHPLC-Q-Orbitrap-HRMS analysis of the water fraction indicated that it was attributed to S-allyl cysteine and S-allyl mercaptocysteine. Keywords: black garlic, metabolomics, S-allyl cysteine, S-allyl mercapto cysteine